The Role of Pyroptosis‐Related Gene Signature and Immune Infiltration in Juvenile Dermatomyositis - Qiao W; Zhu C; Huang D; Liu Y; Wang Z; Zhu T; Song Q; Yang X; Wang Y; Wang Y (Clinical, Cosmetic and Investigational Dermatology)
Weizhou Qiao,1,* Cuiping Zhu,2,* Dan Huang,1 Yue Liu,1 Zengkai Wang,1 Tianjie Zhu,1 Qingyu Song,1 Xu Yang,1 Yueying Wang,1 Yushuang Wang1 1Department of Clinical Laboratory, Central Hospital of Dalian University of Technology, Dalian, 116033, People’s Republic of China; 2Blood Purification Center, Central Hospital of Dalian University of Technology, Dalian, 116033, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weizhou Qiao, Department of Clinical Laboratory, Central Hospital of Dalian University of Technology, No. 826, Southwest Road, Shahekou District, Dalian, Liaoning, 116033, People’s Republic of China, Email qiaoweizhou2024@163.comObjective: Juvenile dermatomyositis (JDM) is a complex autoimmune disease, and its pathogenesis remains poorly understood. Building upon previous research on the immunological and inflammatory aspects of JDM, this study aims to investigate the role of pyroptosis in the pathogenesis of JDM using a comprehensive bioinformatics approach.Methods: Two microarray datasets (GSE3307 and GSE11971) were obtained from the Gene Expression Omnibus database, and a list of 62 pyroptosis-related genes was compiled. Differential gene expression analysis and machine learning analysis were performed to identity the hub pyroptosis-related differentially expressed genes (PR-DEGs). Functional enrichment analysis, immune cell infiltration analysis, gene set variation analysis (GSVA), and gene set enrichment analysis (GSEA) were performed to elucidate the potential roles of PR-DEGs in JDM pathogenesis.Results: A total of 2526 common DEGs were identified, among which 12 PR-DEGs were identified, with CASP1, IRF1, NOD2, and PYCARD identified as hub PR-DEGs. These genes were involved in cytokine production, inflammasome activity, necroptosis, NOD-like receptor signaling, and TNF signaling. Immune infiltration analysis showed increased pro-inflammatory immune cell infiltration in JDM patients, with PR-DEGs positively correlated with various immune cell types. GSVA and GSEA analyses demonstrated the involvement of PR-DEGs in multiple inflammation and immunity-related pathways, with the NOD-like receptor signaling pathway playing a central role.Conclusion: This study highlights the crucial role of pyroptosis in the pathogenesis of JDM, with the identified PR-DEGs potentially contributing to disease development and progression by regulating key inflammatory and immune-related pathways.Keywords: pyroptosis, JDM, immune infiltration analysis, machine learning, diagnostic